Investigating the Effect of ADDIE Model on the Effectiveness of Clinical Education of Operating Room Students - Zardosht, Roghayeh; Malkemes, Susan; Merajikhah, Amirmohammad; Sahebkar, Mohammad (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: As a clinical setting, the operating room (OR) is also a complicated system; there are a lot of contrasts and complexities between the OR environment and other clinical areas regarding the teaching and learning process. Effective teaching in the operating room is clearly one of the most important and yet most challenging and difficult-to-define tasks for any educator. There is no instructional model for operating room students. This study was aimed at developing a clinical education model for OR students, in accordance with ADDIE model. Methods: The ADDIE model was used to guide the development of clinical education in five University of Medical Sciences. The ADDIE model includes five steps of Analysis, Design, Development, Implementation, and Evaluation. Qualitative method, literature review and curriculum assessment was used to generate five step ADDIE model. Results: Conceptual model “gaining of clinical competence and approval” was appeared in analysis step ADDIE model. Presenting educational objectives, learning communication skills and teamwork, performing objective evaluation, administering a comprehensive test, as well as learning from surgical team members and peers were also specified. Conclusions: The findings of the research, in relation to the clinical training of students in the operating room field, indicated the uniqueness of the clinical environment of the operating room and how the student copes with the different conditions of the environment and teamwork in the operating room. The present research led to the design of a model based on the general pattern of educational design(ADDIE model). ADDIE provides a model for common understanding of teamwork to increase aptitude and professional competence of operation room students. It also provides evidence the usefulness of ADDIE model on clinical education for OR students.